The Impact of the Learning Organization on Organizational Maturity and Educational Performance of Faculty Members at Farhangian University, Region 9 of the Country - Shirzad, Samaneh; Khanalipour Roodi, Maedeh (Assessment and Practice in Educational Sciences, 2024)
Learning organizations, by creating a supportive environment and encouraging continuous learning, can contribute to organizational maturity. This maturity not only includes the improvement of organizational processes and culture but also leads to increased collaboration and interaction among faculty members. Therefore, the overall objective of the present study was to examine the impact of the learning organization on organizational maturity and the educational performance of faculty members at Farhangian University, Region 9 of the country. In terms of purpose, this research was applied, and in terms of method, it was descriptive of the survey type. The statistical population consisted of all official faculty members, seconded faculty members, and adjunct instructors of Farhangian University, Region 9, totaling 263 individuals. Based on Cochran’s formula, 156 individuals were selected as the statistical sample using stratified random sampling. Data were collected using the Learning Organization Questionnaire developed by Tavassoli (2012) with 30 items, the Organizational Maturity Questionnaire developed by Afshar (2015) with 33 items, and the Educational Performance Questionnaire developed by Zandi (2013) with 25 items. The face validity and content validity of the instruments were confirmed by experts, and their reliability was calculated using Cronbach’s alpha coefficient, yielding values of 0.89 for the learning organization questionnaire, 0.93 for the organizational maturity questionnaire, and 0.87 for the educational performance questionnaire. Structural equation modeling was used for data analysis. The results indicated that the learning organization had a positive and significant effect on organizational maturity (with a standardized coefficient of 0.57), and the learning organization also had a positive and significant effect on the educational performance of faculty members (with a standardized coefficient of 0.78). Furthermore, the learning organization had a stronger effect on the educational performance of faculty members compared to organizational maturity. The findings of the present study demonstrated that the learning organization has a positive and significant impact on both organizational maturity and the educational performance of faculty members at Farhangian University, Region 9 of the country, and that the proposed model exhibited an appropriate level of goodness of fit. Therefore, it is recommended that more training programs and collaborative opportunities be provided for faculty members, as these measures can contribute to the continuous improvement of educational and research quality at the university and ultimately support the achievement of Farhangian University’s educational and pedagogical objectives.